Product Development of Urban Aquaculture Supporting Equipment Based on Solar Cell Technology and Speed Bump System Using the Design For Manufacture and Assembly (DFMA) Method - Nugraha, Isna; Tranggono, Tranggono; Winursito, Yekti Condro; Dewi, Sinta; Syaifullah, Hafid; Islami, Mega Cattleya Prameswari Annissaa (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
Urban aquaculture, like urban farming, entails using aquaculture technology to transform tiny, previously unutilized pieces of land in highly inhabited metropolitan areas into a useful area. Urban aquaculture, in broad terms, can be defined as the fish farming on small plots of land. Depending on the sort of consumable fish commodity to be grown, urban aquaculture can be implemented through home aquaculture and community aquaculture utilizing a variety of techniques. Creating a mandatory product involves the stages of development and design. At this stage, all product components, production costs, design, and assembly time are taken into account. Through sustainable product design and evaluation, it is possible to address the assembly performance and difficulties in the assembly process, as well as assembly time and costs. The design and development of this product use the Design for Manufacturing and Assembly (DFMA) method. DFMA is a method used to determine the product design with the best time and cost. In general, this method can also be used in development to improve the quality and measure the improvement of urban aquaculture product designs. It is hoped that urban aquaculture will provide an alternative product design to achieve high-quality products and low production costs.